Unique and Attractive Digital Marketing Strategies for MSMEs in Indonesia - Huda, Nurul; Fitriyah, Rizka; Hajar, Hajar; Farid, Salman; Arofah, Vety (CV. Civiliza Publishing, 2025)
Digital marketing has become a key instrument for MSMEs (Micro, Small, and Medium Enterprises) to expand their market reach and compete in the digital era. Although numerous studies have explored digital marketing in general, few have specifically examined unique and engaging strategies that can enhance consumer engagement, brand differentiation, and loyalty in the context of Indonesian MSMEs. This article proposes a strategic framework for distinctive digital marketing by integrating content creativity, personalization, local storytelling, gamification, and omnichannel integration. The research method employed is a literature review and comparative analysis of empirical findings from Indonesian academic journals. The findings indicate that strategies combining interactivity, emotional elements, and adaptation to local characteristics have the potential to significantly improve digital marketing effectiveness. In conclusion, MSMEs need to develop digital marketing strategies that are not only operationally sound but also inspirational. Further field research is recommended to validate this proposed framework.